Estudio de impactos generados por la agricultura en la hacienda Vallejo ubicada en el sector Santa Cruz, cantón Loja - Rojas Hidalgo, Josselyn Thalia (2023)
The present research work was carried out in the Vallejo farm, located in the parish of Malacatos, canton and province of Loja. The main activity carried out on the farm is the cultivation of sugar cane (Saccharum officinarum, L), which is the raw material for the production of panela and guarapo. The research describes the main environmental and social impacts caused by agriculture. To this end, a baseline was established by characterising the abiotic, biotic and socio-economic components, using primary information (data obtained in the field) and secondary information (bibliographic sources). Environmental impacts were identified and assessed through a description of the farm and its activities during the operation phase. With this, the existence of 13 environmental impacts and 3 socio-economic impacts was determined, the quantitative valuation of which was carried out through the application of the Importance Matrix, with which a total of 16 impacts were obtained, of which 93.75% (15) correspond to negative environmental impacts and 6.25% (1) to a positive socio-economic impact. According to the assessment carried out, the greatest negative impact is on the soil resource in a critical state due to the use of agrochemicals in the cultivation of sugar cane, causing the alteration of biodiversity and loss of its fertility, while the main positive impact is the generation of sources of employment due to the fact that the Hacienda needs to hire personnel to carry out the productive activities. With this information, an environmental management plan was designed, which includes seven programmes focused on the prevention, mitigation, management and sustainable rehabilitation of the exploited natural resources. Keywords: agricultural activity, farm, sugarcane, environmental impact, socioeconomic impact, environmental management plan.